Guanidine Hydrochloride-Induced Unfolding of the Three Heme Coordination States of the CO-Sensing Transcription Factor, CooA - Lee, Andrea J. (2009)
CooA is a heme-dependent CO-sensing transcription factor that has three observable heme coordination states. There is some evidence that each CooA heme state has a distinct protein conformation; the goal of this study was to characterize these conformations by measurement of their structural stabilities through guanidine hydrochloride (GuHCl) denaturation. By studying the denaturation processes of the Fe(III) state of WT CooA and several variants, it was possible characterize independent unfolding processes for each domain of CooA. This information was used to compare the unfolding profiles of various CooA heme activation states (Fe(III), Fe(II), and Fe(II)-CO) to show that the heme coordination state changes the stability of the effector binding domain. A mechanism consistent with the data predicts that all CooA coordination states and variants undergo unfolding of the DNA-binding domain between 2 and 3 M GuHCl with a free energy of unfolding of ~17 kJ/mol, while unfolding of the heme domain is variable and dependent on the heme coordination state. The findings support a model in which changes in heme ligation alter the structural stability of the heme domain and dimer interface, but do not alter the stability of the DNA-binding domain. These studies provide evidence that the domains of transcription factors are modular, and that allosteric signaling occurs through changes in the relative positions of the protein domains without affecting the structure of the DNA-binding region.